From Hiroshima to Pahang: A global learning initiative with Hiroshima University for effective communication skills - Wan Noor Farah, Wan Shamsuddin; Siti Asma’, Yaacob; Nur Anisnabila, Dianah (Centre for Modern Languages, 2024)
Gambang, 23 April 2024- More than 130 students enrolled in UHL2432 English for Professional Communication participated in a Global Classroom session via Microsoft Teams, organised by four instructors, under the guidance of Ms. Marziah Ramli as the course coordinator. The session was also facilitated by Ms Wan Noor Farah Wan Shamsuddin, Ms. Siti Asma’ Yaacob, and Ms. Nur Anisnabila Dianah. It was a privilege to welcome Assistant Professor Dr. Wang Tingjia from Hiroshima University’s Writing Centre as the invited speaker.